Addressing the questions of tomorrow: melphalan and new combinations as conditioning regimens before autologous hematopoietic progenitor cell transplantation in multiple myeloma. (May 2013) - Martino, Massimo; Olivieri, Attilio; Offidani, Massimo; Vigna, Ernesto; Moscato, Tiziana; Fedele, Roberta; Montanari, Mauro; Console, Giuseppe; Gentile, Massimo; Messina, Giuseppe; Irrera, Giuseppe; Morabito, Fortunato
<x xml:space="preserve">Abstract</x> Introduction: The role of high-dose chemotherapy (HDC) followed by autologous-progenitor cell transplantation (auto-HPCT) in the treatment of multiple myeloma (MM) continues to evolve in the novel agent era. Administration of high-dose melphalan (HDM) is considered the standard conditioning regimen. Nevertheless, several attempts have recently been made to improve the conditioning phase of the HDC procedure. Areas covered: We reviewed all the reported experiences and illustrated current knowledge in the field of conditioning regimens. Expert opinion: For fit MM patients, HDC followed by auto-HPCT remains the standard of care. The available data confirm that melphalan (MEL) 200 mg/m2 should continue to be considered the gold standard conditioning regimen, with dose reduction based on age and renal function. Targeting exposure to MEL by using area under the curve is a particularly appealing approach that could be explored to maximize efficacy and minimize toxicity of this drug. Other strategies are currently being evaluated in different trials, and the most interesting areas of research involve the incorporation of newer agents like bortezomib (BOR) into conditioning regimens. Moreover, intravenous busulfan has become available and this formulation may reduce toxicity and result in greater efficacy in association with MEL-based conditioning.